2021
DOI: 10.1186/s12870-021-03193-1
|View full text |Cite
|
Sign up to set email alerts
|

The GRAS gene family and its roles in seed development in litchi (Litchi chinensis Sonn)

Abstract: Background The GRAS gene family plays crucial roles in multiple biological processes of plant growth, including seed development, which is related to seedless traits of litchi (Litchi chinensis Sonn.). However, it hasn’t been fully identified and analyzed in litchi, an economic fruit tree cultivated in subtropical regions. Results In this study, 48 LcGRAS proteins were identified and termed according to their chromosomal location. LcGRAS proteins c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 102 publications
(145 reference statements)
0
5
0
Order By: Relevance
“…Members of the GRAS family played an important regulatory role in multiple biological processes [ 63 , 64 ]. In rice, OsGRAS23 was demonstrated to be involved in the drought stress response by binding to the promoters of stress-responsive genes [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Members of the GRAS family played an important regulatory role in multiple biological processes [ 63 , 64 ]. In rice, OsGRAS23 was demonstrated to be involved in the drought stress response by binding to the promoters of stress-responsive genes [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…The GRAS gene family has been identified and analyzed in many model plants, such as A. thaliana ( Lee et al., 2008 ), P. trichocarpa ( Liu and Widmer, 2014 ), and Z. mays ( Guo et al., 2017 ). In addition, their regulation with respect to root and fruit development ( Chen et al., 2021 ) also prompted people to study their function in many economic species, including pepper ( C. annuum L.) ( Liu et al., 2018 ), apple ( M. domestica ) ( Fan et al., 2017 ), and Prunus persica ( Jiang et al., 2022 ). However, the classification of subfamilies is still uncertain, and the number of genes varies greatly among different species.…”
Section: Discussionmentioning
confidence: 99%
“…The development stage, tissue, environmental conditions, and genotype affect expression levels ( Hirsch and Oldroyd, 2009 ), and this is consistent with the results of our qRT-PCR and transcriptome data. Moreover, it has been reported that GRAS is involved in maintaining the normal development of seeds ( Chen et al., 2021 ). The transcriptome data show that LcGRAS is expressed during somatic embryogenesis from the globular embryo stage.…”
Section: Discussionmentioning
confidence: 99%
“…To further identify GRAS gene family members, the GRAS conserved domain HMM model (PF03514) was downloaded from the Pfam database (http://pfam.xfam.org/, accessed on 14 April 2023), using HMMER-3.2.1 (http://hmmer.org/download.html, accessed on 14 April 2023) with an e-value <10 -5 and other parameters by default. After the identification of GRAS genes in P. bournei, the online website ExPASy (https://web.expasy.org/prot-param/, accessed on 26 February 2023) was used to analyze the physical and chemical properties of the GRAS proteins that were identified [65].…”
Section: Identification and Physical And Chemical Property Analysismentioning
confidence: 99%